Bereavement in the Digital Age: The Challenges of Online Sharing and Digital Memory Preservation - Santi, Francesca; Bianchi, Davide (Medicina Historica, 2023)
The advent of digital networks and social networks has significantly affected, not only social behavior and daily life, but also the traditional ways of managing pain, mourning, and commemoration of the deceased. If, in the (recent) past, the presence of the deceased was limited to the memories of people who had known him, or to private photographic images that crystallized his moments of life, in the current technological context the deceased, from being "absent", remains subject "present" in the online spaces that people use every day. Death, pain, and mourning are aspects of fundamental importance for human existence and today, thanks to the development of virtual environments accessible to all, death is brought back into the daily life of individuals. At the same time, digital technologies have given rise to new ways of expressing grief and expressing grief that transcend the traditional notions of mourning "of letting go", to continue their journey, soliciting multiple emotionally and culturally complex questions, involving different disciplines: morality, religion, philosophy, law, and sociology. The authors intend to make some reflections on the most important digital transformations underway concerning the end of life, immortality, the elaboration of mourning and memory, and which seem to outline on the horizon a new idea of approaching and understanding death, rethought and adapted for the digital age.